Thinking Bodies - Shaping Hands : Handeling in Art and Theory of the Late Rembrandtists. - Hadjinicolaou, Yannis (Issn Ser., 2019)
"Thinking Bodies - Shaping Hands focuses on the critical as well as historical dimension of the handling of the brush and of the resulting appearance of colour on the painted surface in art and art theory from the middle of the 17th (above all from 1660) to the dawn of the 18th century in the Netherlands. More specifically, it deals with Rembrandt's last pupils such as Arent de Gelder. "Handeling" describes an active, embodied process that is connected to the motion of the hand with the brush or with any other kind of tool. This term, up to now not sufficiently appreciated in scholarly literature, seems to be fruitful in this context. It is not so much connected with the term "style", as with a prior step, which is equivalent to "manner". At the same time, its meaning in Dutch till today is "action". "Handeling" is an act that could be described as a "form-act". It focuses on Formgestaltung, in which these actions themselves are understood as processes. Examining the "Rembrandtist ideology of painting", this study attempts to reveal the embodied process of painting in the sense of a bodily articulation during the application of colour. This occurs within the productive tension between theory and practice"--